Preclinical antileukemic activity, toxicology, toxicokinetics and formulation development of triptolide derivative MRx102 - Fidler, John M. (2014)
PURPOSE: Triptolide induces cancer cell apoptosis by inhibiting RNA synthesis and signaling pathways like NF-κB. We compared triptolide prodrug MRx102 to triptolide to determine if it displayed comparable efficacy and improved toxicology and toxicokinetic profiles. METHODS: MV4–11 AML cells and cells from AML patients were analyzed for MRx102− and triptolide-induced cytotoxicity/apoptosis. MRx102 and triptolide were compared in toxicology/toxicokinetics studies in rat and dog using a new emulsion formulation. RESULTS: MRx102 induced cytotoxicity in MV4–11 cells (IC(50) = 15.2 nM, 7.29 nM for triptolide) and apoptosis in cells from AML patients (EC(50) = 40.6 nM and 2.13 nM for triptolide). MRx102 and triptolide induced apoptosis in CD34+CD38− AML stem/progenitor cells with a similar difference in activity (EC(50), MRx102 = 40.8 nM, triptolide = 2.14 nM). In a rat toxicology comparison using a new intravenous emulsion formulation, the MRx102 MTD was 4.5 mg/kg for males, 3 mg/kg for females; the triptolide MTD was 0.63 mg/kg for males, 0.317 mg/kg for females. The MRx102 NOAEL was 1.5–3.0 mg/kg, and the triptolide NOAEL was 0.05–0.15 mg/kg. Mean plasma concentrations for both MRx102 and triptolide decreased rapidly from a high C(max) following i.v. injection. Plasma triptolide levels stabilized at a consistent level through 2 hours after MRx102 injection. Triptolide T(1/2,e) values for MRx102-injected rats (~0.85 to ~3.7 hours) were markedly greater than triptolide injected rats (~0.15 to ~0.39 hours), indicating more extended triptolide exposure with MRx102. MRx102 dog toxicology and toxicokinetics results are presented. CONCLUSIONS: MRx102 was 20− to 60-fold safer than triptolide comparing rat NOAELs. This may be due to the improved toxicokinetic profile of MRx102 compared to triptolide using the emulsion formulation, with no high C(max) and more consistent early exposure to triptolide.